Pengaruh Remunerasi terhadap Kualitas Pelayanan Publik - SANCOKO, BAMBANG (UI Scholars Hub, 2011)
This research studies the influence of gift remuneration to the services quality of The State Exchequer Service Office (KPPN) Jakarta I. Remuneration represents one part of the bureaucracy reform programs. KPPN represents the sample office specified by the Department of Finance to administer public service reform programs. The research uses quantitative approach and the method of survey. The result of the research indicates that the remuneration can give motivation to the officers to increase their performance. The achievement is marked by the good performance service (service excellent). The program of remuneration run by the Department of Finance can be operated at direct interconnection with other governmental institutions, especially with the public service.